Response of Ruminal Microbiota-Host Gene Interaction to High-Altitude Environments in Tibetan Sheep. - Sha Y; Ren Y; Zhao S; He Y; Guo X; Pu X; Li W; Liu X; Wang J; Li S (MDPI (Basel, Switzerland), 2022)
Altitude is the main external environmental pressure affecting the production performance of Tibetan sheep, and the adaptive evolution of many years has formed a certain response mechanism. However, there are few reports on the response of ruminal microbiota and host genomes of Tibetan sheep to high-altitude environments. Here, we conducted an integrated analysis of volatile fatty acids (VFAs), microbial diversity (16S rRNA), epithelial morphology, and epithelial transcriptome in the rumen of Tibetan sheep at different altitudes to understand the changes in ruminal microbiota−host interaction in response to high altitude. The differences in the nutritional quality of forage at different altitudes, especially the differences in fiber content (ADF/NDF), led to changes in rumen VFAs of Tibetan sheep, in which the A/P value (acetic acid/propionic acid) was significantly decreased (p < 0.05). In addition, the concentrations of IgA and IgG in Middle-altitude (MA) and High-altitude Tibetan sheep (HA) were significantly increased (p < 0.05), while the concentrations of IgM were significantly increased in MA (p < 0.05). Morphological results showed that the width of the rumen papilla and the thickness of the basal layer increased significantly in HA Tibetan sheep (p < 0.05). The 16S rRNA analysis found that the rumen microbial diversity of Tibetan sheep gradually decreased with increasing altitude, and there were some differences in phylum- and genus-level microbes at the three altitudes. RDA analysis found that the abundance of the Rikenellaceae RC9 gut group and the Ruminococcaceae NK4A214 group increased with altitudes. Furthermore, a functional analysis of the KEGG microbial database found the “lipid metabolism” function of HA Tibetan sheep to be significantly enriched. WGCNA revealed that five gene modules were enriched in “energy production and conversion”, “lipid transport and metabolism”, and “defense mechanisms”, and cooperated with microbiota to regulate rumen fermentation and epithelial immune barrier function, so as to improve the metabolism and immune level of Tibetan sheep at high altitude.
Keywords: Tibetan sheep; altitude; fermentation; host; immune; microbiota; Sheep; Animals; Rumen; Propionates; RNA, Ribosomal, 16S; Altitude; Host Microbial Interactions; Tibet; Fatty Acids, Volatile; Microbiota; Acetates; Immunoglobulin A; Immunoglobulin G; Immunoglobulin M